Analyzing the Financial Sector Nexus Economic Growth of Pakistan: New Insights from ARDL Approach - Kanwal, Amna; Hassan, Muzammal; Butt, Haris (iRASD Journal of Economics, 2023)
In the context of Pakistan, this study looks at how local financial sector expansion and foreign capital inflows affect economic growth. The Error Correction Model is used for short run connections and the ARDL bounds testing technique to cointegration is used for long run interactions, using yearly data series from the Economic Survey of Pakistan and the WDI for the years 1998–2022. Empirical research indicates that foreign capital inflows boost economic expansion. Economic growth is facilitated by both government investment and the expansion of the financial sector. Technology, the human capital pool, and remittances all contribute positively to economic growth. According to the latest report, financial reforms should be implemented by the Pakistani government to increase the effectiveness of the country's financial industry and, eventually, accelerate economic growth.